2014
DOI: 10.1371/journal.pone.0102274
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing FMR1 Gene Mutations as Predictors of Treatment Success in Human In Vitro Fertilization

Abstract: ContextMutations of the fragile X mental retardation 1 (FMR1) gene are associated with distinct ovarian aging patterns.ObjectiveTo confirm in human in vitro fertilization (IVF) that FMR1 affects outcomes, and to determine whether this reflects differences in ovarian aging between FMR1 mutations, egg/embryo quality or an effect on implantation.Design, Setting, PatientsIVF outcomes were investigated in a private infertility center in reference to patients' FMR1 mutations based on a normal range of CGGn = 26–34 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…This finding reinforces the idea that embryo morphology is often an obsolete way to predict ploidy. In donated oocyte recipients, no significant association was found between donor genotypes and clinical pregnancy rates, while in middle-aged patients statistical significance was again found in sub-genotypes showing at least one allele low [56]. An earlier study has similarly demonstrated diminished IVF outcomes linked to specific normal range sub-genotypes, with het-norm/low patients displaying poorer PR as compared to norm (p = 0.001) (Fig.…”
Section: The Fmr1 Gene and Ivf Outcomementioning
confidence: 77%
See 1 more Smart Citation
“…This finding reinforces the idea that embryo morphology is often an obsolete way to predict ploidy. In donated oocyte recipients, no significant association was found between donor genotypes and clinical pregnancy rates, while in middle-aged patients statistical significance was again found in sub-genotypes showing at least one allele low [56]. An earlier study has similarly demonstrated diminished IVF outcomes linked to specific normal range sub-genotypes, with het-norm/low patients displaying poorer PR as compared to norm (p = 0.001) (Fig.…”
Section: The Fmr1 Gene and Ivf Outcomementioning
confidence: 77%
“…In particular, one area of study has been to assess the possible role of FMR1 genotypes as a prognostic marker of outcome in reproductive medicine. In 2014, Kushnir conducted a large investigation on the possible impact of various FMR1 genotypes and subgenotypes on morphological embryo quality in 125 infertile patients (168 IVF cycles and 777 embryos); on 149 IVF cycles (1041 embryos) in potentially fertile women to evaluate ploidy, and on 352 young and infertile women and 179 oocyte donor/recipient cycles to assess the IVF outcome [56]. A low FMR1 sub-genotype (29.6 % of the patients) impacted negatively the embryo morphology and the pregnancy rate despite of the age of the mother.…”
Section: The Fmr1 Gene and Ivf Outcomementioning
confidence: 99%
“…Their IVF patients, thus, were very favorably selected and to a significant degree excluded women with low FOR. In contrast, the typical patient selected in one of our recent studies was 39.7 years old, had a mean FSH of 11.2 mIU/mL, and mean AMH of only 1.5 ng/mL [10]. Thus, Bank's patient population provided less power to detect a possible association with impaired FOR and for this reason the observed association was weaker than previously reported in a more at-risk population.…”
Section: Recent Studiesmentioning
confidence: 55%
“…Patients with <100 CGG repeats have significantly lower milestones of ovarian response and fertilization rates than those with ≥100 CGG repeats [28], and it has even been postulated that distinct FMR1 genotypes might explain differences in IVF outcome between races [29]. Kushnir et al [30] suggested that the FMR1 gene may negatively impact oocyte/ embryo quality and thus IVF pregnancy rates particularly among those patients that have an allele with low repeats independently from ploidy. Therefore, the number of repeats found on the FMR1 gene may have a role not only in the prognosis of IVF success through embryo quality expectations but also in treatment adjustments since some patients may be initially managed as low responders [28][29][30].…”
Section: Outcomes Of Assisted Reproductionmentioning
confidence: 99%
“…Kushnir et al [30] suggested that the FMR1 gene may negatively impact oocyte/ embryo quality and thus IVF pregnancy rates particularly among those patients that have an allele with low repeats independently from ploidy. Therefore, the number of repeats found on the FMR1 gene may have a role not only in the prognosis of IVF success through embryo quality expectations but also in treatment adjustments since some patients may be initially managed as low responders [28][29][30]. In the future, infertility clinics might become one of the main places where affected families are identified.…”
Section: Outcomes Of Assisted Reproductionmentioning
confidence: 99%